2018
DOI: 10.1021/acs.inorgchem.8b02249
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Patterns in Nucleation and Growth of Icosahedral Core of [AunAg44–n(SC6H3F2)30]4– (n = 0–12) via ab Initio Synthesis: Continuously Tunable Composition Control

Abstract: An ab initio one-pot synthesis of the bimetallic clusters [Au n Ag 44−n (SC 6 H 3 F 2 ) 30 ] 4− (abbreviated (AuAg) 44 ; n ≤ 12) is reported. The mixed-metal (AuAg) 44 clusters, synthesized with different reactant Au/Ag ratios, exhibit a fractal-like distribution, suggesting that nucleation of the icosahedral core is a fractal growth process. X-ray crystallographic studies provided unambiguous evidence that the doped Au atoms occupy the icosahedral sites and the maximal doping is 12. The number of Au atoms (n)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The DFT structure is in agreement with the crystal structure of Au 12 Ag 32 (SR) 30 directly prepared from mononuclear precursors by Zheng et al 28,29 In a recent report of alloy clusters formed in a related "one-pot ab initio synthesis", Zheng et al showed by X-ray crystallography that any number of Au doping (from 0 to 12) in Ag 44 (SR) 30 clusters leads to Au exchange in the icosahedral core. 29 By contrast, Xie et al have suggested that 12 Au atoms exchange on the surface (staple) of the preformed Ag 44 (SR) 30 clusters (rather than in its core) when the exchange is mediated by Au(SR) 2 Cl-type thiolates. 30 In a related study, Burgi et al have inferred that over longer times, silver exchange occurs preferentially in the core of a Au 38 (SR) 24 cluster rather than on its staples.…”
Section: Introductionsupporting
confidence: 83%
“…The DFT structure is in agreement with the crystal structure of Au 12 Ag 32 (SR) 30 directly prepared from mononuclear precursors by Zheng et al 28,29 In a recent report of alloy clusters formed in a related "one-pot ab initio synthesis", Zheng et al showed by X-ray crystallography that any number of Au doping (from 0 to 12) in Ag 44 (SR) 30 clusters leads to Au exchange in the icosahedral core. 29 By contrast, Xie et al have suggested that 12 Au atoms exchange on the surface (staple) of the preformed Ag 44 (SR) 30 clusters (rather than in its core) when the exchange is mediated by Au(SR) 2 Cl-type thiolates. 30 In a related study, Burgi et al have inferred that over longer times, silver exchange occurs preferentially in the core of a Au 38 (SR) 24 cluster rather than on its staples.…”
Section: Introductionsupporting
confidence: 83%
“…, co-reduction of a mixture of metal salts). 33 The Ag 44− x Au x (SR) 30 clusters used in our experiments were synthesized by the co-reduction method and their UV/Vis spectra resemble those of the previously reported Ag 44− x Au x (SR) 30 clusters which consist of twelve 17 or nearly twelve Au atoms. 33 Therefore, it is very likely that the number of Au atoms in the Ag 44− x Au x (SR) 30 clusters used in our experiments is also twelve, approximately.…”
Section: Resultsmentioning
confidence: 54%
“…5B ) indicate that the number of Au atoms in them is 0–12 and that these Au atoms are located in the innermost, hollow icosahedral shell. 33 It is also known that when the number of Ag atoms in Ag 44− x Au x (SR) 30 clusters is significantly less than twelve, the UV/Vis absorption spectra of such clusters are similar to those of Ag 44 (SR) 30 and that it is not possible to incorporate more than twelve Au atoms in Ag 44 (SR) 30 by direct synthesis ( i.e. , co-reduction of a mixture of metal salts).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 It is also worth noting that the reported alloy Au x Ag 44− x NCs so far exclusively adopted the M–S framework of [Ag 44 (SR) 30 ] 4− , where up to 12 Ag atoms are substitutable by Au atoms. 35,40–42 Therefore, [Ag 44 (SR) 30 ] 4− , [Au 44 (SR) 26 ] 2− and their alloy NCs provide an ideal platform for decoding the composition dependent alloying chemistry at the molecular and atomic levels, although an efficient synthetic method should be developed for fine tuning the composition of alloy Au x Ag 44− x NCs in a wide composition range.…”
Section: Introductionmentioning
confidence: 99%